FOLIAR APPLICATION OF NANOCERIA ENHANCES ARSENIC STRESS TOLERANCE BY MODULATING THE METABOLITES OF THREE VARIETIES OF MUNGBEAN (VIGNA RADIATA L) - Okunlola, Gideon; Olatunji, Olusanya; Adeosun, Ifeoluwapo; Adebisi, Saheed; Jimoh, Mulikat; Folorunso, Sakeenat; Mustafa, Abdulwakiil (FUDMA JOURNAL OF SCIENCES, 2025)
Global food security is seriously threatened by arsenic pollution in agricultural systems, particularly for leguminous crops like mungbean (Vigna radiata L.), which are highly susceptible to heavy metal poisoning.  This work uses advanced gas chromatography-mass spectrometry (GC-MS) profiling to investigate how cerium oxide nanoparticles (nanoceria) can help reverse the metabolic disturbances caused by arsenic.  Three commercially important mungbean cultivars were examined with varying concentrations of arsenic stress (from 0 to 100 mg/L) and nanoceria (100 mg/L) applied to their leaves.  Comparing the treated controls to those under arsenic stress, it was observed that the application of nanoceria markedly enhanced the production of important stress-responsive metabolites: D-mannose increased by 58%, oleic acid increased by 34%, and lycopene increased by an astounding 72%. Clear dose-dependent metabolic patterns were identified by the GC-MS analysis, and phenolic compounds and fatty acid derivatives stood out as vital markers to mitigate arsenic stress.  These findings provide insight into the dual functions of nanoceria as a metabolic regulator and antioxidant, presenting a viable nano-enabled strategy for sustainable crop production in heavy metal-contaminated regions.
Keywords: Heavy Metal Stress; Nanoagriculture; Oxidative Stress Management; Metabolic Profiling; Phytoremediation